Inhibition of vascular adhesion protein‐1 enhances the anti‐tumor effects of immune checkpoint inhibitors - Kinoshita, Tomonari (Cancer Sci, 2021)
Modulation of the immunosuppressive tumor microenvironment (TME) is essential for enhancing the anti‐tumor effects of immune checkpoint inhibitors (ICIs). Adhesion molecules and enzymes such as vascular adhesion protein‐1 (VAP‐1), which are expressed in some cancers and tumor vascular endothelial cells, may be involved in the generation of an immunosuppressive TME. In this study, the role of VAP‐1 in TME was investigated in 2 murine colon cancer models and human cancer cells. Intraperitoneal administration of the VAP‐1‐specific inhibitor U‐V296 inhibited murine tumor growth by enhancing IFN‐γ‐producing tumor antigen‐specific CD8(+) T cells. U‐V296 exhibited significant synergistic anti‐tumor effects with ICIs. In the TME of mice treated with U‐V296, the expression of genes associated with M2‐like macrophages, Th2 cells (Il4, Retnla, and Irf4), angiogenesis (Pecam1), and fibrosis (Acta2, Loxl2) were significantly decreased, and the Th1/Th2 balance was increased. H(2)O(2), an enzymatic product of VAP‐1, which promoted the production of IL‐4 by mouse Th2 and inhibited IFN‐γ by mouse Th1 and human tumor‐infiltrating lymphocytes, was decreased in tumors and CD31(+) tumor vascular endothelial cells in the TMEs of mice treated with VAP‐1 inhibitor. TCGA database analysis showed that VAP‐1 expression was a negative prognostic factor in human cancers, exhibiting a significant positive correlation with IL‐4, IL4R, and IL‐13 expression and a negative correlation with IFN‐γ expression. These results indicated that VAP‐1 is involved in the immunosuppressive TMEs through H(2)O(2)‐associated Th2/M2 conditions and may be an attractive target for the development of combination cancer immunotherapy with ICIs.